2009
DOI: 10.4314/afrrev.v3i1.43554
|View full text |Cite
|
Sign up to set email alerts
|

Perception and Attitudes of Christian Youths towards Condom Use (Implications for HIV/AIDs in Nigeria)

Abstract: The study examined religiousity, perception and attitude towards condom use among Christian youths in Ile Ife, Nigeria with the aim of examining the implications on HIV/AIDs. A structured questionnaire based on Likert-type scales was employed to rate respondents' attitudes. A total of 260 youths were interviewed, but 210 (80.8%) were found to be sexually active as at the time of the survey. Those who had sexual initiation before the age of 20 years were 42.9%, while less than 5% had ever gone for HIV test. Gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…However, studies in Africa have found that the level of religiosity is a significant predictor of good attitude towards condom use, abstinence and the knowledge towards HIV prevention. 20 , 21 , 22 …”
Section: Discussionmentioning
confidence: 99%
“…However, studies in Africa have found that the level of religiosity is a significant predictor of good attitude towards condom use, abstinence and the knowledge towards HIV prevention. 20 , 21 , 22 …”
Section: Discussionmentioning
confidence: 99%